Solution-processable donor–π–acceptor type thieno[3, 2-b]thiophene derivatives; synthesis, photophysical properties and applications. Issue 29 (14th July 2022) - Isci, Recep; Wan, Li; Topal, Sebahat; Gunturkun, Dilara; Campbell, Alasdair James; Ozturk, Turan
Abstract : Two new D–π–A-type fluorescent materials with nearly quantitative quantum yields, possessing thieno[3, 2- b ]thiophene, triphenylamine and boron units, were synthesized and their devices were fabricated via a solution process. Abstract : Two novel donor-π-acceptor (D–π–A)-type pull–push materials, M1 and M2, having triphenylamine as a donor and dimesitylboron as an acceptor, linked through a thieno[3, 2- b ]thiophene (TT) π-conjugated spacer bearing different functional substituents, such as –PhCN and –Ph, were synthesized and fabricated via a solution process for OLED applications. They exhibited mega Stokes shifts of 120 nm and emissions both in the solid-state and in solution. The monomers M1 and M2 had strong intramolecular charge-transfer behaviors; the solid-state quantum yields were recorded to be 76 and 72% and the solution quantum efficiencies were determined to be 100 and 95%, respectively. The solution-processed OLEDs were fabricated using low turn-on voltages, which had performances with maximum power, current and external quantum efficiencies of around 8 lm W −1, 14.1 cd A −1 and 4.78%, respectively, displaying emission colors from blue to green and yellowish green. The materials had strong fluorescence emission colors between yellowish and bluish under UV irradiation.